sThe Bioremediation of Industrial Effluents by Phanerochaete Chrysosporium: The COD, TOC Removal Efficiency and Biochemical Assessment for Dreissena Polymorpha - Serdar, Osman; Yildirim, Numan; Onder Erguven, Gokhan; Ketenalp, Zozan; Cikcikoglu Yildirim, Nuran; Durmus, Barbaros (Wiley-V C H Verlag Gmbh, 2024)
Bioremediation is one of the cheapest and easy method for biological treatment for most kind of industial wastewater. Bioremediation potential of the Phanerochaete chrysosporium for industrial wastewater from Industrial Zone Wastewater plant in Mardin, Turkey, was evaluated. The chemical oxygen demand (COD) and total organic carbon (TOC) reduction efficiencies of P. chrysoporium of on wastewater studied using biomarkers such as catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), Thiobarbituric Acid (TBARS) and reduced glutathione (GSH) levels in Dreissena polymorpha. The level of TBARS, a marker of lipid peroxidation was found to be high because of wastewater exposure after treatment. TBARS levels decreased (from 20.2 to 31.6 and from 20.8 to 37.5). GSH levels (from 52.3 to 15.9), CAT levels (from, 119.7 to 15.3 and from 91.1 to 13.4) SOD levels (from 3.8 to 0.9 and from 3.4 to 1.2) and GPX activity (from 177.2 to 104.4 and 174.2 to 100.5) decreased in the wastewater exposure groups during 24 and 96(th) hour compared to the control groups. GSH levels, CAT, SOD and GPX activity increased after treatment by P. chrysosporium. Results indicate that industrial wastewater caused oxidative stress in Dreissena polymorpha. The findings revealed that the highest removal efficiency for COD and TOC, at 86.3 % and 80.3 % respectively, occurred in the 1/20 diluted medium. P. chrysosporium has proven to be effective in the bioremediation of wastewater from the Industrial Zone Changes in biochemical parameters before and after bioremediation showed that antioxidant parameters such as CAT, SOD, GPx activities and GSH and TBARS levels can be used as biomarker to evaluate bioremediation efficiency.
Keywords: Bioremediation; Biomarkers; D. Polymorpha; Industial zone; P. chrysosporium